PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PROFITABILITAS, DAN PERTUMBUHAN ASET TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BEI TAHUN 2010-2013 - Okty Anindias Sari, 11.05.52.0111; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
This study aimed to examine and analyze the influence of Structure Asset, Size, Profitability and Growth Assets for Debt to Equity Ratio in Real Estate and Property companies listed in Indonesia Stock Exchange in 2010-2013. The population used in this study is the Real Estate and Property companies listed in Indonesia Stock Exchange ( IDX ) during 2010-2013. Sampling method used is purposive sampling, with a total sample of 116 companies.The research data analysis using multiple linear regression starting with test data normality, the classical assumption test consisting of multicoloniarity test, test and test heterokadasitas autocorrelation. Further testing of the strength of the model by using the coefficient of determination and F test of hypothesis testing using t test with significance at 5 % alpha. The test results showed that the variable structure assets negative and a significant on the Debt to Equity Ratio, Size positive and no significant on the Debt to Equity Ratio, Profitability positive and significant on the Debt to Equity Ratio and Growth Asset positive and no significant on Debt to Equity Ratio.Keywords: Structure Asset, Size, Profitability, Growth Assets and Debt to Equity Ratio